Peripapillary retinal nerve fiber layer and choroidal thickness in cirrhosis patients - Akdemir,M.Orcun (2015)
ABSTRACT Purpose: To evaluate the effect of cirrhosis on peripapillary retinal nerve fiber layer and choroidal thickness with enhanced depth imaging optical coherence tomography. Methods: This cross sectional, single center study was undertaken at Bulent Ecevit University Ophthalmology department with the participation of internal medicine, Gastroenterology department. Patients who were treated with the diagnosis of cirrhosis (n=75) were examined in the ophthalmology clinic. Age and sex matched patients (n=50) who were healthy and met the inclusion, exclusion criteria were included in the study. Complete ophthalmological examination included visual acuity with Snellen chart, intraocular pressure measurement with applanation tonometry, biomicroscopy of anterior and posterior segments, gonioscopy, axial length measurement, visual field examination, peripapillary retinal nerve fiber layer, central macular and subfoveal choroidal thickness measurements. Results: The difference between intraocular pressure values was not statistically significant between cirrhosis and control group (p=0.843). However, mean peripapillary retinal nerve fiber layer thickness was significantly thinner in cirrhosis group in all regions (p<0.001) and subfoveal choroidal thickness was significantly thinner in cirrhosis group also (p<0.001). Moreover, central macular thickness of cirrhosis group was significantly thicker than the control group (p=0.001). Conclusion: Peripapillary retinal nerve fiber layer and subfoveal choroidal thickness was significantly thinner in cirrhosis patients.